Upaya Peningkatan Kemampuan Literasi Baca Tulis Santri di Pesantren Baitul Arqam Aceh Besar: The Efforts to Improve Reading and Writing Literacy Skills of Students at Baitul Arqam Islamic Boarding School Aceh Besar - Nazariah, Nazariah; Helmanda, Cut Mawar; Yani, Muhammad (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Literacy is essentially the ability of a person to read and write. Knowledge cannot be solely provided by teachers. Therefore, students are expected to be able to explore and seek knowledge and information from various sources to enrich their understanding. In Indonesia, there is still a weak understanding of multiple texts, or, in other words, a lack of comprehension of information. This indicates that the reading and writing literacy skills of Indonesian students are below the global average, especially in the current digital era. Recognizing this situation, the community service team consisting of permanent lecturers from University Muhammadiyah Aceh and I would like to develop reading and writing literacy at Baitul Arqam Islamic Boarding School Aceh Besar. This community service project began on February 19, 2023, and continued indefinitely. The target audience of this project was all middle school-level students. The method used in this community service project was community-based research (CBR), utilizing action research and participatory research approaches. Through guidance and support, the outcome was a book titled "Aku Menulis Aku Berdaya", which consisted of writings by the students of Baitul Arqam. The implications of the service outcomes can strengthen cooperation with neighborhood educational institutions and madrasas to increase the impact of this program, develop more materials and content specifically geared toward students’ literacy needs, including materials based on religion and culture, involve parents and guardians of students in the learning process to support literacy practices in the home environment, and periodically monitor the literacy development of students